Lze dosahovat kvality bez ohledu na životní prostředí? - Turková, Daniela (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2009)
Tato bakalářská práce se zabývá problematikou dosažení kvality produktů v různých oblastech průmyslové výroby České Republiky, důraz je kladen na zpracování odpadů, od výroby přes užití až po odstranění výrobků při dodržování stanovených norem. Součástí je také návrh možného řešení výroby co možná nejméně zatěžující životní prostředí.

This bachelor thesis deals with the subject of meeting quality requirements in various fields of industrial production in the Czech Republic with the emphasis put on scrap and waste materials processing; from manufacturing a product through its use until its disposal while maintaining specific standards/norms. The thesis also contains a proposal of a potential production plan with a maximally reduced negative impact on the environment.
Quality and Environment management system
Keywords: Kvalita; odpady; životní prostředí; normy 14000; hutní průmysl; automobilový průmysl; výroba a zpracování plastů.; Quality; wastes; environment; 14000 quality standards; smelting industry; automotive industry; plastic production and processing.